Pulmonary sclerosing pneumocytoma: Cytomorphology and immunoprofile. Issue 6 (5th February 2020) - Maleki, Zahra; Muller, Stephanie; Layfield, Lester; Siddiqui, Momin T.; Rekhtman, Natasha; Pantanowitz, Liron
Abstract : Background: Sclerosing pneumocytoma (SP) is a rare, benign pulmonary neoplasm. To the authors' knowledge, the current study is the first to evaluate the cytomorphology and immunoprofile of SP in a series. Methods: A total of 9 fine‐needle aspiration cases of SP (7 of which were computed tomography guided and 2 of which were endobronchial ultrasound guided) including histopathology and immunohistochemistry were collected from 5 institutions. Results: The female‐to‐male ratio was 3.5:1, and the mean age of the patients was 54 years (range, 27‐73 years). All cases presented as lung nodules, with a mean size of 2.2 cm (range, 1.1‐5 cm), and were interpreted as atypical on rapid on‐site evaluation. The final diagnoses were favor adenocarcinoma (1 case), well‐differentiated lung adenocarcinoma (2 cases), low‐grade epithelial neoplasm (2 cases), and sclerosing pneumocytoma (4 cases). Samples were moderately cellular, and consisted of round epithelioid cells with clear cell features, columnar cells, and spindle cells. A papillary arrangement with prominent hyalinized fibrovascular cores was the most common architectural pattern, followed by flat sheets and acinar formations. Tumor cells demonstrated mild, focally moderate nuclear pleomorphism with prominent nucleoli, hyperchromasia, nuclear elongation, nuclear overlap, and occasional nuclear inclusions and grooves. The background consisted of foamy macrophages (9 cases), hemosiderin pigment (6 cases), and lymphoid aggregates (3 cases) with no mitoses and/or necrosis. The surface cells and underlying round cells were positive for both thyroid transcription factor 1 and epithelial membrane antigen in all cases, which was the most notable immunohistochemical finding. Conclusions: Cytomorphological findings of SP overlap with those of well‐differentiated lung adenocarcinoma. Awareness of these cytomorphologic findings and the distinct immunoprofile of the 2 cell types found in SP should prevent a misdiagnosis and aggressive treatment. Abstract : Sclerosing pneumocytoma (SP) is a rare, benign, pulmonary neoplasm of primitive respiratory epithelial origin that shares cytomorphologic features with well‐differentiated lung adenocarcinoma. A papillary arrangement with prominent hyalinized fibrovascular cores, flat sheets, and acinar formations composed of round epithelioid cells with clear cell features, columnar cells, and spindle cells with immunoreactivity of surface cells and underlying round cells for both thyroid transcription factor 1 and epithelial membrane antigen are features distinguishing SP from lung adenocarcinoma.